BENTUK SAMBUNGAN STRUKTUR BAMBU PADA PERENCANAAN HOTEL RESOR - Cheris, Rika; Ramadhan , Fajri; Imbardi, Imbardi (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
Bamboo is a building construction material used throughout the archipelago and is the oldest building material. The use of bamboo construction materials is suitable for sustainable development strategies and green architecture campaigns. Indonesia is one of the countries that is very rich in types of bamboo that grow according to local soil conditions, especially in West Sumatra. There are many types of bamboo that are found for various uses in building construction. The use of bamboo in simple structures is common. However, for large structures there are still very few. This is likely due to a lack of knowledge regarding the use and process of preservation and connections. For now, researchers will focus more on forms of bamboo connections that are commonly used and are quite durable. There have been many commonly used bamboo connections, but this time the researchers will make them for large buildings. Meanwhile, for the structure of this Resort building, the type of joints and connections between bamboo structures are key in ensuring the transfer of structural loads to the bamboo building. The aim of this research is to look for bamboo connections in the structure of resort hotel buildings. The research method used is descriptive qualitative to describe the appropriate type of connection in planning a resort hotel in the Rupat Island tourist area. The results of this research are several forms of joints in bamboo material which is an alternative material in this area as a form of attraction in resort hotel design.